Anatomical and histochemical features of the vegetative organs of Dioscorea polystachya (Dioscoreaceae) - Jiang, Zhiguo; Xiong, Huanhuan; Li, Youzhi; Zhao, Chongnan; Li, Teng; Zhang, Mengdi; Zhang, Xia; Zhang, Xia; Yang, Chaodong; Zhou, Cunyu (Emirates Journal of Food and Agriculture, 2022)
We investigated the anatomical and histochemical features of Dioscorea polystachya (Dioscoreaceae), an important food crop in China. The primary structures of D. polystachya include vertical tubers, adventitious roots, twining aerial stems, and leaves with bulblets. The vertical tubers have storage parenchyma with scattered vascular bundles, a cortical meristerm zone, and phellem. The cortical meristerm zone acts as a cambium to thicken the tubers. The twining stems and petioles both have a sclerenchyma layer with vascular bundles, while the blades have palisade tissues and spongy tissues covered by a cuticle. The roots have stele, an endodermis, and an exodermis. The scattered vascular bundles and phellem in the vertical tubers, the sclerenchyma layers and cuticles in the stems and leaves, and the endodermis and exodermis in the roots facilitated the adaptation of D. polystachya to terrestrial environments. The cortical meristerm zone thickens the tubers, which improves cultivation techniques. These structural features help to clarify the complex taxonomy, evolutionary history, and phylogenetic relationships of D. polystachya